Heritages, Identities, and Policy in the Metropolitan Area of Lisbon - Silvano, Filomena (2014)
In a world that has moved away from narratives based on the idea of progress, the past has established itself as a place of reference: confirming to ourselves that what we were is indispensible for sustaining what we think we are. The recovery of the past is thus one of the most common symbolic instruments used in negotiating identities. The cultural practices that have recourse to representation mechanisms that call on the past in order to consider the present always end up translating themselves, insofar as they fragment, reorganize and interpret it in their transformation, or, to use a formula that has become unavoidable, in their “invention”. Patrimonialization is one such practice. It associates the notion of heritage – which is not a given fact, but rather a socially constructed classification, and therefore one that is constantly being negotiated – with specific objects that come to serve as cultural representations of the groups who consider themselves to be their rightful owners. In the Lisbon Metropolitan Area, as in other ethnographic contexts, patrimonialization encompasses things as diverse as landscapes, monuments, popular architecture, handicrafts, local feast days/processions/pilgrimages and people; all things that can, once transformed into material representations of the past, serve as arguments for the identity fictions of the people who inhabit them.